Masa Simpan Kerang Hijau (Perna viridis) pada Suhu Ruang dengan Uji Organoleptik dan Uji pH - Rifky Ardytiandi; Muhammad Mush'ab Al Mujahid; Rama Aditya Putra; Evi Liviawaty (JURNAL RISET RUMPUN ILMU HEWANI, 2024)
Green mussels (Pernan viridis) are a marine resource that has good protein content. Of these advantages, there are disadvantages, namely the relatively short shelf life. The method used in this research is organoleptic testing (including texture, appearance, color and odor), pH and weight loss. The aim of this research is to determine the storage time of green mussels at room temperature. The results obtained in the organoleptic test where the appearance of the buffer lasted for 4 hours, the aroma for 4 hours, and the texture for 5 hours. The initial pH was found to be 7.14 after storage for 12 hours at room temperature, the pH was 6.53 and there was a decrease in weight loss of 11 g. From this research it was found that the longer the storage time, the quality of green mussels (verna piridis) will decrease.